The Role of Capital Adequacy Standards According to Basel Accords (1,2) In the Credit Risks: Case Study (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Commercial banks represent the main pivot in financing national economic activity and its development. The capital represents safety margin to depositors and represents a defense line that protects bank work from dangers. Basel committee requirements represent protection and comprehensive supervision to bank activities for depositors, debtors and the bank. It provides trust in bank dealings and tackles activities of high dangers. The most prominent of these requirements are capital adequacy that concerns bank management and supervision and auditing bodies such as the central bank and protecting banks that suffer weakness in its vital important borrowing activity that reflects weakness in implementing borrowing policy .The purpose of political borrowing guarantee security borrowing that the bank give it security supervision continual on the process of borrowing of the whole stages ,in spite of its differences from bank to another but its agree with in general framework that consisting of its contents .The data of this study show that capital adequacy standard in Rafidean Bank cannot be applied currently because of its small current capital (25) milliard dinar which is a small amount to result that capital adequacy =1/2% almost . And the need of the bank to support its credit position with increasing transparency and clarity to improve its classification in Iraq extent (12%) in credit classification agencies. The recommendation includes the evolution policy and procedures instrument of loans that goes to the constancy of the bank and to assume the responsibility towards strategic risks of loans to continuation and supervision among standards level of qualification and efficiency to enormous averages benefit advantages according to the acceptable risks .The bank has to measure capital adequacy throughout the significance to the entire risks and measure it throughout the capital adequacy standards in order to be confirmed that the bank committed to application of this standards.